SOMATOTYPOLOGICAL PARAMETERS OF THE BODY IN MEN WITH BENIGN NEVI - Haddad, N.B.Yo.; Mateshuk-Vatseba, L.R.; Maievskyi О.Ye.; Kotsyura, O.O.; Nalizhytyi, A.A. (World of Medicine and Biology, 2022)
The study analyzed the features of the components and type of somatotype according to Heath Carter and indicators of the component composition of body weight in Ukrainian men with benign nevi. In most cases, practically healthy men have significantly lower values of the mesomorphic component of the somatotype and the muscular component of body weight and higher values of the ectomorphic component of the somatotype. Patients with melanocyte benign simple nevi have significantly higher values of somatotypological indicators (except for the ectomorphic component of somatotype) and indicators of the component composition of body weight than patients with melanocyte benign dysplastic nevi.